Imaging for Hemorrhoidal Disease: Navigating Rectal Artery Embolization from Planning to Follow-up - Lindquist, Jonathan; Hart, James; Marchak, Katherine; Bent Robinson, Eduardo; Trivedi, Premal (Seminars in Interventional Radiology, 2024)
Hemorrhoid disease is very common, affecting greater than one-third of adults. Conservative management and several office-based procedures are useful in the treatment of internal hemorrhoids. Patients with refractory hemorrhoid disease have traditionally been treated with surgical hemorrhoidectomy. Rectal artery embolization has emerged as an alternative to surgical hemorrhoidectomy and has been shown to be safe and effective in case series and clinical trials completed over the past decade. Embolization has significantly less postprocedure pain when compared with surgical hemorrhoidectomy with similar outcomes. Pre- and postprocedure imaging are not routinely performed. Intraprocedural imaging consists of selective catheterization of the superior rectal arteries from the inferior mesenteric artery, and the middle rectal arteries from the internal iliac artery. The inferior rectal artery is seldom embolized due to the supply of the levator ani muscle and skin. To date, intermediate and large particles and fibered and nonfibered coils have been used successfully.
Keywords: internal hemorrhoids; rectal artery embolization; hemorrhage; rectal bleeding; interventional radiology